Vertical handle force (Rowing Biomechanics Newsletter, 2013)
Last year, the first pilot study on the vertical oar forces was done with the BioRowTel system and now the authors discuss the results. They conclude: Vertical forces at the handle are quite small and even smaller at the blade (about 10N ~ 1kgF), so they do not really contribute to vertical movements of the rower-boat system. A significant part of the handle force is directed vertically: from 7%at pitch 4o up to 14%at 8o. Variable (lateral) pitch could be recommended to minimize vertical forces and make the blade path in the water more horizontal.